Modern Methods and Approaches in Teaching English Grammar in Middle and High School (Texas Journal of Multidisciplinary Studies, 2025)
This study examines contemporary pedagogical approaches to English grammar instruction in secondary education. The research investigates the effectiveness of integrated methodologies that combine communicative strategies, technological tools, and student-centered activities. Using a mixed-methods design with 180 participants, the study compares traditional grammar teaching methods with modern approaches incorporating task-based learning and digital resources. Results demonstrate significant improvements in grammatical accuracy and communicative competence among students exposed to contemporary methods. The findings suggest that combining explicit instruction with meaningful communicative practice creates optimal conditions for grammar acquisition. The study concludes with practical recommendations for implementing these approaches in diverse classroom settings, emphasizing the importance of teacher training and appropriate resource allocation.